ANALISIS PENGARUH KEPEMIMPINAN TERHADAP DINAS KETENAGAKERJAAN KOTA MEDAN - Geryl Valeri Evans; Levirisky Siahaan; Sindy Maulana, Tania Alexandra Tambunan (STKIP Subang, 2025)
This study aims to analyze and empirically test the influence of leadership on the performance of the Medan City Manpower Office. The Manpower Office plays a crucial role in administering government affairs in the employment sector, which directly impacts public welfare and the investment climate in Medan City. Therefore, optimal performance is essential, one of which is strongly suspected to be influenced by leadership quality. This study uses a quantitative approach by distributing questionnaires to employees of the Medan City Manpower Office as a sample. The collected data are analyzed using simple or multiple linear regression methods (adjust to your design, for example: multiple linear regression analysis) to measure the contribution of leadership variables to performance variables. The results of this study are expected to provide empirical evidence regarding the significance of leadership's influence on increasing the effectiveness and efficiency of the office's work, as well as provide practical recommendations for the Medan City Government in its efforts to improve leadership quality within the bureaucracy, particularly in the Manpower Office.